2000
DOI: 10.1029/2000jc900054
|View full text |Cite
|
Sign up to set email alerts
|

Loop Current rings and the deep circulation in the Gulf of Mexico

Abstract: Abstract.A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 22 publications
9
54
0
1
Order By: Relevance
“…and life spans (≈ 10~17 months) are reasonable in view of observations. Romanou et al also examined deep eddies, and confirm Sturges et al's [993] and Welsh and Inoue's [2000] findings that these eddies are spun up by Loop Current's extension and ring-shedding. Figure 2 and Table show that MICOM results in the Yucatan Channel have similar characteristics to those from POM and OPA.…”
Section: Loop Current and Yucatan Channel Flow Variabilitysupporting
confidence: 62%
“…and life spans (≈ 10~17 months) are reasonable in view of observations. Romanou et al also examined deep eddies, and confirm Sturges et al's [993] and Welsh and Inoue's [2000] findings that these eddies are spun up by Loop Current's extension and ring-shedding. Figure 2 and Table show that MICOM results in the Yucatan Channel have similar characteristics to those from POM and OPA.…”
Section: Loop Current and Yucatan Channel Flow Variabilitysupporting
confidence: 62%
“…Welsh and Inoue (2000) found that the deep cyclone survives longer than the anticyclone in the western Gulf, suggesting a mean cyclonic abyssal flow. Tenreiro et al (2018) show observational evidence of large-scale fluctuations of relative vorticity in the deep layer as expected from modons trapped below westward-moving LC rings.…”
Section: Introductionmentioning
confidence: 99%
“…In the deep abyssal plain of the western basin, numerical studies suggest that the LC rings induce eddies in the bottom layer via vortex stretching, resulting in an anticyclone (cyclone) in the leading (trailing) edge moving westward and locked to the surface eddy (Hurlburt and Thompson 1982;Sturges et al 1993;Welsh and Inoue 2000). Welsh and Inoue (2000) found that the deep cyclone survives longer than the anticyclone in the western Gulf, suggesting a mean cyclonic abyssal flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sigsbee abyssal plain occupies most of the central portion of the basin and is characterized by thin turbidite layers (Bryant et al, 1991). The surface circulation is dominated by the Loop Current and interaction with eddies (Welsh and Inoue, 2000), in general the water column is thermally stratified and displays space and time variability along the continental shelf (Monreal-Gómez and Salas de León, 1997).…”
Section: Methodsmentioning
confidence: 99%